2014
DOI: 10.4028/www.scientific.net/msf.783-786.1889
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cooperativity in Metallic Glass Forming Liquids

Abstract: The relation between fragility and cooperativity of atomic motion in bulk metallic glass forming liquids is studied based on the bond strength-coordination number fluctuation model. The model describes the temperature dependence of the viscosity in terms of the mean values of the bond strength, coordination number and their fluctuations of the structural units that form the melt. According to the model, the cooperativity increases with the increase of fragility. The model estimates that the magnitude of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…( 2), we obtain an expression of the cooperativity N B as a function of the fragility m. This is given by N B = ln(10)m/C. Our previous studies have confirmed this interrelationship and the applicability of this relation to glass-forming materials [12,13].…”
Section: Thermec 2016supporting
confidence: 54%
“…( 2), we obtain an expression of the cooperativity N B as a function of the fragility m. This is given by N B = ln(10)m/C. Our previous studies have confirmed this interrelationship and the applicability of this relation to glass-forming materials [12,13].…”
Section: Thermec 2016supporting
confidence: 54%
“…It has been suggested that a group about 10 atoms are involved in the collective atomic transport processes occurring in the supercooled liquid state [9]. Regarding the cooperativity of atomic dynamics in supercooled liquids, our analysis based on the Bond Strength-Coordination Number Fluctuation model [21] indicates that the number of structural units involved vary with temperature [22]. The connection of such a cooperativity with the fragility has been also investigated [23].…”
Section: Structural Alloysmentioning
confidence: 87%
“…In a previous study, Eq. ( 5) has been used to study the cooperativity of MGFLs [14]. There it was shown that at the glass transition temperature 𝐶𝐶 = 1, NB varies roughly between 10 and 50.…”
Section: The Bond Strength-coordination Number Fluctuation Model: a B...mentioning
confidence: 99%